2021
DOI: 10.1029/2020jb021061
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical Property Modifications by Alteration in a Volcanic Sequence at IODP Site U1513, Naturaliste Plateau

Abstract: Petrophysical properties of volcanic rocks are controlled by lithology and subsequent modification by alteration processes. Investigating the linkages, using a range of different techniques, are important to establish how petrophysical properties can inform about the alteration state of volcanic rocks. Here, we compile petrophysical data and correlate these with geochemical and mineralogical analyses acquired from a volcanic sequence on the Naturaliste Plateau, offshore southwest Australia (International Ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 103 publications
0
13
1
Order By: Relevance
“…Kaolinite is generally considered to form by strong leaching of feldspar, mica and pyroxene in a humid climate and acid medium [4,29]. A warm and humid climate is conducive to the formation and preservation of kaolinite [30].…”
Section: Clay Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaolinite is generally considered to form by strong leaching of feldspar, mica and pyroxene in a humid climate and acid medium [4,29]. A warm and humid climate is conducive to the formation and preservation of kaolinite [30].…”
Section: Clay Mineralsmentioning
confidence: 99%
“…They are significant indicators of the sedimentary environment, climatic conditions and diagenesis. Therefore, through the study of clay minerals and their assemblages, it is possible to understand characteristics related to provenance, paleoclimate, sedimentary environment and diagenetic environment, and to help reconstruct the processes of sedimentation and diagenesis [1][2][3][4]. Extracting information on environmental evolution from the fluctuations in element content in sediments is a commonly used method to study environmental changes.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical weathering increases the value to 100, with clay formation, secondary mineralization, and textural changes. Strongly weathered source rocks and sediments are commonly related to hot and wet climatic conditions and hydrothermal activity [61,62]. The CIA values for the Permian igneous and sedimentary samples vary in a range from 26.4 to 50.1 (Figure 10e).…”
Section: Weathering and Maturity Analysismentioning
confidence: 99%
“…The Bouma-like and volcanic-rich sandstone sequences were likely deposited by turbidity currents at a relatively deep water depth, but thin sandstone layers with cross or parallel beddings imply shallow marine deposition. The Lower Permian volcanic rocks on the northern margin show textural deformation and secondary mineralization resulting from weathering and alteration, which are likely attributable to interactions between volcanic minerals and meteoric, seawater, and hydrothermal fluids (e.g., [62]). On the southern areas of the Chaiwopu Depression, sedimentary structures and facies provide limited information but suggest that massive conglomerates mixed with sandstones can be attributed to deposits in the alluvial fan system (e.g., [64]), which are commonly observed with the dynamic growth of normal fault zones in rift basins [65].…”
Section: Depositional Environmentmentioning
confidence: 99%
“…It contains the first in-situ volcanic rocks and a complete sequence of volcaniclastic-rich sedimentary rocks (Hauterivian-early Aptian), which spans the transition from syn-to post-rift phase during the rifting and breakup between Greater India and Australia-Antarctica. [6][7][8][9] described hydrothermal alteration throughout the volcanic and volcaniclastic-rich sequences. [3] confirmed that the Naturaliste Plateau subsided from subaerial setting to mid-lower bathyal depths during the Early Cretaceous.…”
Section: Introductionmentioning
confidence: 99%